2019
DOI: 10.3390/ijms20246254
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin E2/EP Signaling in the Tumor Microenvironment of Colorectal Cancer

Abstract: The number of colorectal cancer (CRC) patients is increasing worldwide. Accumulating evidence has shown that the tumor microenvironment (TME), including macrophages, neutrophils, and fibroblasts, plays an important role in the development and progression of CRC. Although targeting the TME could be a promising therapeutic approach, the mechanisms by which inflammatory cells promote CRC tumorigenesis are not well understood. When inflammation occurs in tissues, prostaglandin E2 (PGE2) is generated from arachidon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
103
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(106 citation statements)
references
References 105 publications
0
103
0
3
Order By: Relevance
“…In support of future combination clinical trials, Albu et al showed that EP4 antagonism combined with either Treg depletion or with an antibody to CTLA-4 provided superior tumor control to either monotherapy (Albu et al, 2017). Cancer clinical trials to evaluate EP4 inhibitors are recruiting in trials of Grapiprant (ARY-007) in combination with pembrolizumab in subjects with either advanced MSS colorectal cancers (NCT03658772) or, in a separate trial in advanced NSCLC (NCT03696212) (Mizuno et al, 2019;Take et al, 2020). E7046 is being examined in a rectal cancer trial (NCT03152370) and BMS 986310 plus nivolumab is being investigated in a phase 1 trial in advanced solid tumors (NCT03661632).…”
Section: Future Directionsmentioning
confidence: 99%
“…In support of future combination clinical trials, Albu et al showed that EP4 antagonism combined with either Treg depletion or with an antibody to CTLA-4 provided superior tumor control to either monotherapy (Albu et al, 2017). Cancer clinical trials to evaluate EP4 inhibitors are recruiting in trials of Grapiprant (ARY-007) in combination with pembrolizumab in subjects with either advanced MSS colorectal cancers (NCT03658772) or, in a separate trial in advanced NSCLC (NCT03696212) (Mizuno et al, 2019;Take et al, 2020). E7046 is being examined in a rectal cancer trial (NCT03152370) and BMS 986310 plus nivolumab is being investigated in a phase 1 trial in advanced solid tumors (NCT03661632).…”
Section: Future Directionsmentioning
confidence: 99%
“…However, phospholipases A 2 (PLA 2 ) are the main cellular regulators of PUFA release, maintaining the homeostatic levels of several free PUFAs, and in particular of those that are precursors of mediators with pro-inflammatory properties, such as arachidonic acid (AA, 20:4 n-6). In the inflammation process, AA is released by PLA 2 activity, and prostaglandin E 2 (PGE 2 ) is subsequently generated from arachidonic acid by the enzyme cyclooxygenase-2 (COX-2) [ 34 , 35 ]. One of the mechanisms that Tregs uses to suppress T cell activity is PGE 2 production, which can be reversed by COX-2 inhibitors [ 36 ].…”
Section: Lipid Metabolism Impacts Immune Activation Against Tumor mentioning
confidence: 99%
“…These M2 macrophages secrete anti-inflammatory IL-10, and PGE2 supporting the migration of endothelial cells and angiogenesis [218]. In addition to promoting angiogenesis, PGE2 released from dying cells also provokes the recruitment of macrophages, CAFs, and neutrophils into TME and suppresses the antitumor functions of T cells and natural killer cells [219].…”
Section: Communication Between Cancer Cells and Surrounding Stromal Cmentioning
confidence: 99%